2013
DOI: 10.1186/1471-2458-13-613
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, health behaviours and health: a population-based associational study

Abstract: BackgroundSocial capital is associated with health behaviours and health. Our objective was to explore how different dimensions of social capital and health-related behaviours are associated, and whether health behaviours mediate this association between social capital and self-rated health and psychological well-being.MethodsWe used data from the Health 2000 Survey (n=8028) of the adult population in Finland. The response rate varied between 87% (interview) and 77% (the last self-administered questionnaire). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
4
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(158 citation statements)
references
References 37 publications
11
129
4
8
Order By: Relevance
“…Although alcohol consumption is harmful to people's health, 24 in some situations and quantities, the alcohol consumption habit can be related to greater participation in social activities and better functional conditionsl. 25 In this study, the variable did not remain in the final model though.…”
Section: Discussionmentioning
confidence: 99%
“…Although alcohol consumption is harmful to people's health, 24 in some situations and quantities, the alcohol consumption habit can be related to greater participation in social activities and better functional conditionsl. 25 In this study, the variable did not remain in the final model though.…”
Section: Discussionmentioning
confidence: 99%
“…affirmation), peer pressure for healthy behaviours or access to health information. There is evidence indicating that social support and health are related 65 and that social support can promote better health behaviours when employed alongside goal-setting and self-monitoring. Ferranti et al 66 found that social support is positively correlated with a good diet and increased physical activity.…”
Section: Social Supportmentioning
confidence: 99%
“…through reinforcement, encouragement, motivation, feedback, empathy, role-modelling and increased self-efficacy), particularly in combination with goal-setting and self-monitoring, 65 and has been identified as a component of the majority of effective behaviour change interventions. 71 Additionally, continued professional support is related to better WLM.…”
Section: Social Supportmentioning
confidence: 99%
“…Neither social support nor 21 deprivation appeared to have any effect on SRH regardless of reporting heterogeneity. Empirical evidence has consistently demonstrated a relationship between social 48 capital and self-rated health (SRH) (Chen and Meng, 2015; Giordano et al, 2012; Kawachi et 49 al., 1999; Kawachi and Berkman, 2014; Koutsogeorgou et al, 2015;Nieminen et al, 2013 Nieminen et al, , 50 2010, but because there is no 'gold standard' of how to measure social capital, the strength 51 of the association is uncertain. A simple definition of social capital is: the "resources that are 52 accessed by individuals as a result of their membership of a network or a group" (Kawachi 53 and Berkman, 2014).…”
mentioning
confidence: 99%